Constructing Student Knowledge Amidst the Era of Artificial Intelligence: A Sociology of Education Perspective - Soffi, Dewi Ariyanti; Masruroh, Binti; Widowati (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
Artificial Intelligence (AI) has infiltrated the education domain, offering enhanced learning effectiveness. This study examines the construction of student knowledge in the era of Artificial Intelligence (AI) development from a sociological perspective in education. This research employed a descriptive qualitative approach, incorporating literature studies and data collection techniques. The results indicate that AI facilitates the construction of student knowledge. In the externalization stage, students build knowledge by expressing ideas outside themselves or through thinking. In the objectivation stage, ideas become part of social reality through interaction. In the internalization stage, social knowledge is adopted back into the individual. Artificial Intelligence provides access to extensive learning resources, facilitates online discussions, and personalizes learning according to individual and group needs. However, issues emerge, such as the digital literacy gap, differences in access to technology, and potential algorithmic bias, which can affect the validity of the knowledge built. From a sociology of education perspective, while AI plays an important role, its use must be carefully considered to avoid individual mindset errors caused by the technology. This study contributes to the sociology of education by showing how AI supports student knowledge construction through externalization, objectivation, and internalization. It highlights AI’s role as a social medium in learning while also addressing issues, such as digital literacy gaps, unequal access, and algorithmic bias, offering insights for educators, policymakers, and technology developers.